Abstract of paper 'On the dwellings of working men in cities, and the efforts that have been made to improve them' - Urlin, R. Denny (Statistical and Social Inquiry Society of Ireland, 1865)
I have undertaken to bring forward this subject, not that I hope to state anything which shall be new, but because the subject appears one which should no longer be overlooked by this Society.
On the dwellings of working men in cities, and the efforts that have been made to improve them
Read Wednesday, 16th December, 1863
Keywords: Living standards of industrial workers; Condition of urban dwellings; 314.15